Peningkatan Hasil Belajar Siswa Melalui Pendekatan Cooperative Learning Tipe Student Team Achievement Division (STAD) Pada Mata Pelajaran IPS Kelas IV SD Negeri 135 Rejang Lebong - Emmi Fauziah (AR-RIAYAH : Jurnal Pendidikan Dasar, 2018)
This research is motivated by the phenomena that occur in the learning process, especially the subjects of Social Sciences, including the poor communication between teachers and students, teacher domination which has passive impact on students in the classroom, and lack of reinforcement and reward for students. Classroom Action Research (CAR) consists of 2 cycles, each of which consists of two to three meetings. The stages in each cycle consist of the stages of planning, implementation, observation / observation, and reflection. The research subjects were fourth grade students of RejangLebong Elementary School 135 consisting of 24 people in the 2016/2017 school year. The results were obtained that in the first cycle students' learning outcomes averaged 60.79 and the percentage of classical learning completeness was 58.33%. In the second cycle there were no more weaknesses that occurred in cycle I. The learning outcomes in the second cycle obtained an average of 72.47 with the percentage of classical learning completeness 87.5%. This fulfills the completeness criteria, ie 85% of students get a value of ,07.0 and the learning process is said to be completed individually if students get a value of ≥7. Based on the results of these studies, the Cooperative Learning Approach Student Team Achievement Division (STAD) type can improve learning outcomes, student activities, and teacher activities and the quality of the social studies learning process.